Collaborative, pooled and harmonized study designs for epidemiologic research: challenges and opportunities. (8th February 2018) - Lesko, Catherine R; Jacobson, Lisa P; Althoff, Keri N; Abraham, Alison G; Gange, Stephen J; Moore, Richard D; Modur, Sharada; Lau, Bryan
Abstract: Collaborative study designs (CSDs) that combine individual-level data from multiple independent contributing studies (ICSs) are becoming much more common due to their many advantages: increased statistical power through large sample sizes; increased ability to investigate effect heterogeneity due to diversity of participants; cost-efficiency through capitalizing on existing data; and ability to foster cooperative research and training of junior investigators. CSDs also present surmountable political, logistical and methodological challenges. Data harmonization may result in a reduced set of common data elements, but opportunities exist to leverage heterogeneous data across ICSs to investigate measurement error and residual confounding. Combining data from different study designs is an art, which motivates methods development. Diverse study samples, both across and within ICSs, prompt questions about the generalizability of results from CSDs. However, CSDs present unique opportunities to describe population health across person, place and time in a consistent fashion, and to explicitly generalize results to target populations of public health interest. Additional analytic challenges exist when analysing CSD data, because mechanisms by which systematic biases (e.g. information bias, confounding bias) arise may vary across ICSs, but multidisciplinary research teams are ready to tackle these challenges. CSDs are a powerful tool that, when properly harnessed, permits research that was not previously possible.